Simon Bolivar : Travels and Transformations of a Cultural Icon - Reyes, Ana María (College teacher); Shanahan, Maureen G. (Book collections on Project MUSE., 2016)
This title shows us how and why Simón Bolívar is still a major icon in Latin American culture. Cinema, politics, painting, literature, religion, and opera are all touched and marked by 'El Libertador' who is still very much an active force in Latin America. In this volume, an array of international and interdisciplinary scholars shows the ways Bolívar has appeared over the last two centuries in painting, fiction, poetry, music, film, festival, dance, city planning, and even reliquary adoration.